1994
DOI: 10.1128/aem.60.1.264-270.1994
|View full text |Cite
|
Sign up to set email alerts
|

Significant Biogenesis of Chlorinated Aromatics by Fungi in Natural Environments

Abstract: Common wood-and forest litter-degrading fungi produce chlorinated anisyl metabolites. These compounds, which are structurally related to xenobiotic chloroaromatics, occur at high concentrations of approximately 75 mg of chlorinated anisyl metabolites kg of wood-' or litter-' in the environment. The widespread ability among common fungi to produce large amounts of chlorinated aromatic compounds in the environment makes us conclude that these kinds of compounds can no longer be considered to originate mainly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(47 citation statements)
references
References 39 publications
0
46
0
1
Order By: Relevance
“…The enzyme has a ten times higher affinity for the latter compound [201]. P. ostreatus does not produce significant amounts of veratryl alcohol; however, when grown on either synthetic glucose medium or in fungal associated wood samples [32], anisaldehyde could be detected (unpublished results), indicating an active AAO coupled H202-generating system.…”
Section: The Production Of H20 2 With Aryl Alcohol Oxidase (Aao)mentioning
confidence: 95%
See 1 more Smart Citation
“…The enzyme has a ten times higher affinity for the latter compound [201]. P. ostreatus does not produce significant amounts of veratryl alcohol; however, when grown on either synthetic glucose medium or in fungal associated wood samples [32], anisaldehyde could be detected (unpublished results), indicating an active AAO coupled H202-generating system.…”
Section: The Production Of H20 2 With Aryl Alcohol Oxidase (Aao)mentioning
confidence: 95%
“…Table 1 shows that several basidiomycetes also produce chlorinated anisyl alcohols and aldehydes. The chlorinated anisyl metabolites (CAM) are produced both under laboratory conditions [31, 40,80] and in the environment [32]. It is anticipated that phenylalanine or tyrosine is also a precursor in the biosynthesis of CAM compounds.…”
Section: Chlorination Of Aromatic Compoundsmentioning
confidence: 99%
“…The final moisture content of all the inoculated soil samples was 36% (w/w). After addition of the sludge, the microbial biomass to soil ratio was approximately 0.4 g/kg dry weight in the UN 1 and AC 1 samples and 1.6 g/kg (dry wt) in the UN 4 and AC 4 samples. The 2-MCP-contaminated soil samples, both sterile and unsterilized (i.e., native) soil, that were not inoculated with sludge served as controls.…”
Section: Inoculation Of Soil With Acclimated and Unacclimated Sludgementioning
confidence: 96%
“…H. fasciculare is a known producer of organohalogens. De Jong et al [5] reported the formation of 3,5-dichloro-p-anisyl alcohol and 3,5-dichloro-p-anisyl aldehyde by this fungus up to a concentration of 17 mg per liter when grown in liquid cultures. Grif-¢th et al [7] reported the production of 3,5-dichloro-4-hydroxy-(2P,6P-dichloro-4P-methoxymethylphenyl) benzoate in a concentration of 8.0 mg per liter when grown on an agar medium.…”
Section: Introductionmentioning
confidence: 95%
“…Chemicals and syntheses of authentic compounds All chemicals were purchased from Merck, Darmstadt, Germany, unless stated otherwise. The syntheses of 3,5-dichloro-p-anisyl alcohol and 3,5-dichlorop-anisaldehyde were described by de Jong et al [5]. The synthesis of 3,5-dichloro-p-anisic acid was described by Swarts et al [12].…”
Section: Glucosementioning
confidence: 99%